Hybrid Optimization Method for Design of Rail Passengers Safety and Comfort System. (2016) - Galuszka, Adam; Swierniak, Andrzej; Hejczyk, Tomasz; Mlynczak, Jakub
Abstract: This paper presents a concept of an Integrated System of Supporting Information Management in Passenger Traffic. The novelty of the system is an integration of six modules: video-monitoring, counting passenger flows, dynamic information for passengers, the central processing unit, surveillance center and vehicle diagnostics into one coherent solution. Basing on expert evaluations, we propose to present configuration design problem of the system as three-objectives discrete static optimization problem. Then, a new hybrid method joining properties of weighted sum and ɛ-constraint methods is proposed. The hybrid approach matches our problem. Solution selections based on hybrid method, using two exemplary cases, are shown.